Income Segregation and Local Progressive Taxation: Empirical Evidence from Switzerland - Kurt Schmidheiny (Hamburg Institute of International Economics (HWWA), 2003)
Swiss metropolitan areas are comprised of a system of communities with considerable fiscal autonomy. This study investigates how the income tax differentials across communities in an urban area affect the households` location decisions. Data from the urban agglomeration of Basel for the year 1997 is used. This unique data set contains tax information from all households that moved either within the city center of Basel or from the city center to the outskirts. The community choice of the households is investigated within the framework of the random utility maximization model (RUM). A theoretical model with progressive income taxation is developed to identify the household preferences applied in the RUM. Different econometric spezifications of the error term structure, such as conditional logit, nested logit and multinomial probit are compared. The empirical results show that rich households are significantly and substantially more likely to move to low-tax communities than poor households.
Keywords: H73; H71; R23; R20; 330; Location Choice; Discrete Choice; Multinomial Probit; Mixed Logit; Spatial Autocorrelation; Income Segregation; Gemeindesteuer; Einkommensteuer; Steuerbelastung; Wohnstandort; Stadt-Land-Beziehung; Basel